Twitter’s Fake News Discourses Around Climate Change and Global Warming - Al-Rawi, Ahmed; OʼKeefe, Derrick; Kane, Oumar; Bizimana, Aimé-Jules (Frontiers in Communication, 2021)
In this empirical study, we collected about 6.8 million tweets that mentioned “fake news”, and we extracted references to climate change and/or global warming to understand the public discourses around these two issues. Using a mixed method, the study’s findings show that there is a clear politically polarized discussion on climate change. We found that the majority of tweets focus on the United States context though references to other Western coutnries are often made. The anti-Liberal or anti-Democratic online community was more active on Twitter than the anti-conservative or anti-Republican community. Also, more than half the examined most retweeted posts contained claims about climate change being a natural cycle or even denying it exists, while about a third of these tweets stated that climate change was anthropogenic. The implications of the study are discussed, we argue that fake news as a term has a hollow meaning as it is used as a buzzword to discredit opponents and further the political agenda of different parties not only in the United States but also in other Western countries like Australia.